PEMANFAATAN PATI UBI JALAR SEBAGAI BAHAN BAKU PEMBUATAN PATI BERKATION DENGAN PROSES HIDROLISIS - Nana Dyah Siswati; Siltje Rivana; Zuroida Novi A. (BUANA SAINS, 2007)
Cationic starch is as modified starch that is used in paper industry as glue, additive and surface sizing agent. Modification of starch will happen under gelatinization temperature. To avoid the gelatinization an alkaline salt of Na2SO4 is need. This experiment was done by using sweet potato starch reacted with nitrogen containing dimethyl ammonium chloride. Effects of adding Na2SO4 at concentrations of 0,5, 1, 1,5, 2, 2,5% of the total material weight and at 40; 50; 60; 70;80 oC heating temperature were measured for this study. To indicate the best quality of cationic starch DS (Substitution Degree) standard grade available in paper industry between 0,02 – 0,04.was used. The best result was reached on concentration of 1% Na2SO4 and 40 oC heating temperature, the yield was 91,71% and DS grade was 0.036 (meeting the DS standard grade)